From private phones to public screens: Cross-media recontextualization of chat discourse in the case of the Austrian ÖVP corruption affair - Pfurtscheller, Daniel (Frontiers in Communication, 2022)
The profound establishment of text-based interaction via mobile messenger services has not only changed interpersonal communication, but also reshaped its quotability. Drawing on the notion of recontextualization, this paper investigates the cross-media transfer-and-transformation of text messages from their former confidential contexts into public media environments. The data are drawn from the media discourse on the corruption affair of the Austrian People’s Party (ÖVP), which was triggered by the publication of confidential chat messages in the fall of 2021. Comparing the presentation of text messages in the journalistic media with their intertextual antecedents (in investigative files and related documents), the analysis highlights several linguistic and visual transformations. The findings demonstrate how formerly private chat interactions have been represented in media discourse and reveal different multimodal forms of cross-media quotation, ranging from linguistic replay and visual restaging to elaborate forms in which text messaging is audio-visually re-enacted. These modes of cross-media recontextualization differ in the degree to which the mediality of the digital chat discourse is conveyed or imitated. Through this media linguistic lens, the study contributes to the theory of recontextualization and raises the question what concept of quotation and re-enactment is appropriate and linguistically due in the sage of a deep digitalization of everyday communication.